My brother the killer : a family story - Sharkey, Alix (Harper, an imprint of HarperCollinsPublishers, 2021)
A journalist recounts his own journey to come to terms with his brother's terrible crimes of sexual violence against women-and to find justice for the 15-year-old girl he kidnapped and murdered.